Tinjauan Hukum Islam Tentang Kekerasan Non Fisik Terhadap Anak Dalam Keluarga: Studi Kasus di Gampong Pisang Kecamatan Labuhan Haji Kabupaten Aceh Selatan - ENDIRA, NOVI (State Islamic University (UIN) Ar-Raniry, 2016)
This paper aimed to find out non-physical forms of violence against children occurring in Kampung Pisang of Labuhan Haji District, South Aceh and the view of Islamic law on non-physical violence against children in the family. Findings showed that the violence against children in the village was caused by the lack of knowledge of the parents, making them easily committed such violence. Most of the violence was non-physical such as parents scolding, cursing, and talking to children with abusive and obscene words that were not appropriate for them. The reason for such violence to happen was largely because the children did not want to do what was told by the parents. In summary, the occurrence of non-physical violence in Kampung Pisang was due to simple problems done by the children.